STRATEGI STABILISASI KINERJA PASAR CENGKEH NASIONAL / Stabilitation Strategy of National Clove Market Performance - Agus Wahyudi (Perspektif, 2016)
Clove (Syzigium aromaticum L. Marr. and Perr.) is one of the main raw materials in the kretek cigarette industry. The development of the clove market performance experienced ups and downs in the last four decades. The demand for clove almost consistently grew, while the production fluctuate in the short term and tends to increased in the last ten years. This review is aimed to analyze the market performance stabilization strategy through the development of national program and supply management policies. The analytical framework used in developing the strategy are (1) the analysis of the situation, (2) analysis of strategies for achieving the desired situation, and (3) analysis of the policies needed to accelerate the realization of the situation. Clove market situation that occurs at this time shows nearly balanced, in which the demand for cigarette industry can almost be met from national production in the long term. Therefore, the strategies are to encourage national production by pushing plant productivity through intensification and rehabilitation of existing plants. Area extention will naturally happen if the situation of balance between demand and supply maintainedin the long term. Price fluctuations that occur because of their short-term fluctuations in the production of each year handled through supply chain management. Therefore technical policy, institutional and financial required to facilitate the access of farmers to acquire bank financing such schemes to harvest and post-harvest financing and implementation of warehouse receipt system to provide alternatives to farmers when the price fall.